The family caregiver’s discourse on the hospitalization of the elderly with Alzheimer’s disease O discurso do cuidador familiar sobre a hospitalização do idoso com doença de Alzheimer - Gabriela Pizelli Mocco Grillo; Aline Miranda da Fonseca Marins; Rosâne Mello (Revista de Pesquisa Cuidado é Fundamental Online)
Resumo